Identification and Characterization of Two Quiescent Porin Genes, nmpC and ompN, in Escherichia coli B(E) - Prilipov, Alexej (American Society for Microbiology, 1998)
The genomic DNA of the B(E) strain of Escherichia coli has been scrutinized to detect porin genes that have not been identified so far. Southern blot analysis yielded two DNA segments which proved highly homologous to, yet distinct from, the ompC, ompF, and phoE porin genes. The two genes were cloned and sequenced. One of them, designated ompN, encodes a porin which, due to low levels of expression, has eluded prior identification. The functional properties (single-channel conductance) of the OmpN porin, purified to homogeneity, closely resemble those of the OmpC porin from E. coli K-12. The second DNA fragment detected corresponds to the nmpC gene, which, due to an insertion of an IS1 element in its coding region, is not expressed in E. coli B(E).